2020
DOI: 10.3389/fphys.2020.590962
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise−Mediated Changes in Redox Profile Contribute to Muscle Remodeling After Passive Hand-Rolled Cornhusk Cigarette Smoke Exposure

Abstract: Consumption of non-traditional cigarettes has increased considerably worldwide, and they can induce skeletal muscle dysfunction. Physical exercise has been demonstrated to be important for prevention and treatment of smoking-related diseases. Therfore, the aim of this study was to investigate the effects of combined physical exercise (aerobic plus resistance exercise) on muscle histoarchitecture and oxidative stress in the animals exposed chronically to smoke from hand-rolled cornhusk cigarette (HRCC). Male Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Similar to other tobacco products that might not be machine manufactured, such as bidis in India and some kreteks in Indonesia, 1 straw cigarettes are often seen as more natural and less harmful than cigarettes by consumers. 2 However, studies among mice found that exposure to straw cigarette smoke causes damage similar to any other cigarette. [2][3][4] Beyond health dangers, straw cigarette production also raises socioeconomic concerns at the national level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other tobacco products that might not be machine manufactured, such as bidis in India and some kreteks in Indonesia, 1 straw cigarettes are often seen as more natural and less harmful than cigarettes by consumers. 2 However, studies among mice found that exposure to straw cigarette smoke causes damage similar to any other cigarette. [2][3][4] Beyond health dangers, straw cigarette production also raises socioeconomic concerns at the national level.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, studies among mice found that exposure to straw cigarette smoke causes damage similar to any other cigarette. [2][3][4] Beyond health dangers, straw cigarette production also raises socioeconomic concerns at the national level. In 2019, the Brazilian Federal Police exposed several cases of tax evasion involving straw cigarette companies that had resulted in a government loss of R$100 million.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation